ANALISIS AIR LIMBAH PADA DAPUR PRAKTEK DI POLITEKNIK PARIWISATA MAKASSAR - Musawantoro, Muhammad; Shafany, Mustifa (UNIVERSITAS NEGERI MAKASSAR, 2019)
The importance of research is to provide a description of wastewater content in Makassar polytechnics in the kitchen, through experimental research methods, by taking wastewater samples from practical kitchens, laboratory test results provide results data obtained from chemical Oxygen Demand supply, wastewater discharged directly into sewers Will not meet the requirements for wastewater quality standards. The wastewater treatment model in polytechnics is still not feasible and is not environmentally friendly, steps need to be taken to make wastewater installations.